Model Predictive Control for Three-Level Cascaded H-bridge D-STATCOM. Issue 1 (2nd January 2020) - Srinivasa Rao, Y.; Pathak, M. K.
ABSTRACT: In this paper, a model predictive control (MPC) is investigated for a three-level H-bridge D-STATCOM. To predict the future behavior, a discrete-time model of the D-STATCOM is used. Here in the MPC, a single objective cost function is used to avoid the weighted factors in a multivariable objective function, which in turn leads to complex optimization problem. A single objective cost function controls the error in the reference and actual current. A separate proportional integral controller and a capacitor balancing algorithm are used to self-support the DC capacitor voltage under load variation. The reference current for D-STATCOM is generated by using d-q control strategy for the compensation of reactive power and current harmonics. The switching state which minimizes the current error and the corresponding redundant switching state which meets for the DC capacitor voltage balancing are applied at the next sampling instant. The performance of the investigated MPC control scheme is developed in MATLAB-SIMULINK model and steady-state performance is experimentally verified for non-linear load.